Taking the plunge: When is best for hot water immersion to complement exercise in heat and hypoxia - Dennis, M. C.; Goods, P. S. R.; Binnie, M. J.; Girard, O.; Wallman, K. E.; Dawson, B. T.; Peeling, P. (Journal of Sports Sciences, 2022)
This investigation assessed the psycho-physiological and performance effects of hot water immersion (HWI) implemented either before or after a repeated-sprint training in hypoxia (RSH) session conducted in the heat. Ten participants completed three RSH trials (3 × 10 × 5-s sprints), conducted at 40°C and simulated altitude of 3000 m. A 30-min monitoring period preceded and followed all exercise sessions. In PRE, the pre-exercise period was HWI, and the post-exercise period was seated rest in temperate conditions. This combination was reversed in POST. In CON, participants were seated in temperate conditions for both periods. Compared to CON, PRE elicited a reduction in power output during each repeated-sprint set (14.8-16.2%, all p < 0.001), and a significantly higher core temperature (Tc) during the pre-exercise period and throughout the exercise session (p < 0.001 and p = 0.025, respectively). In POST, power output and Tc until the end of exercise were similar to CON, with Tc higher at the conclusion of the post-exercise period (p < 0.001). Time across the entire protocol spent =38.5°C Tc was significantly longer in PRE (48.1 ± 22.5 min) than POST (31.0 ± 11.3 min, p = 0.05) and CON (15.8 ± 16.3 min, p < 0.001). Employing HWI following RSH conducted in the heat provides effective outcomes regarding physiological strain and cycling performance when compared to pre-exercise or no HWI.